PERBEDAAN HASIL BELAJAR SISWA DALAM MODEL PEMBELAJARAN LANGSUNG DENGAN MENGGUNAKAN MODUL DAN TANPA MENGGUNAKAN MODUL - Asri Rahmawati Azizah, (Pendidikan Ekonomi, 2011)
The study was intended to find out whether there was a difference of learning outcomes for the ten-year-students who learned through direct instruction with modules and those without modules in accounting class of SMKN I Sooko, Mojokerto. The population was all tenth graders of accounting classes, and  those belonged to accounting class I and II were chosen as the sample. The data were collected from tests. The data were then analyzed using t-test. The result shows that there is a significant difference of learning outcomes for the students who studied through direct instruction with modules and for those without modules. Furthermore, the direct instruction with modules enabled the students to achieve higher scores.